Personal satellite services : next-generation satellite networking and communication systems : 6th International Conference, PSATS 2014, Genoa, Italy, July 28-29, 2014, Revised selected papers /: next-generation satellite networking and communication systems : 6th International Conference, PSATS 2014, Genoa, Italy, July 28-29, 2014, Revised selected papers. (2016) - Unknown
No abstract available